2013
DOI: 10.4172/1948-5956.1000199
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Antioxidant Studies of Etoposide Treated Kidney of Rat

Abstract: Materials and Methods Animals and ethical clearanceAdult male albino rats of Wistar strain were used for the study. Animals were weighing about 220-250g obtained from Rajudyog biotechnology division Maharashtra, India were used. The animal studies were carried out upon institutional animal ethical committee approval. DrugsEtoposide was procured from Dabur India Ltd. Bovine serum albumin, reduced and oxidized GSH, thio barbituaric acid (TBA), butylated hydroxytolune (BHT), L-gammaglutamyl-p-nitroanilidehydrochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
2
3
0
Order By: Relevance
“…Electron dense may be secondary lysosomes which result from engulfing of aggregated proteins or degenerated organelles as mitochondria. This also confirmed by Kamble et al, (2013) [33] who illustrated presence of secondary lysosomes during their study of the effect of etoposide (cancer chemotherapeutic agent) on the rat kidney as an indication of degenerative activity.…”
Section: Discussionsupporting
confidence: 80%
“…Electron dense may be secondary lysosomes which result from engulfing of aggregated proteins or degenerated organelles as mitochondria. This also confirmed by Kamble et al, (2013) [33] who illustrated presence of secondary lysosomes during their study of the effect of etoposide (cancer chemotherapeutic agent) on the rat kidney as an indication of degenerative activity.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, in our histopathological analysis of kidneys we found that ETP administration caused congestion of renal blood vessels, chronic inflammatory cell infiltration (predominantly lymphocytes and fibroblast), marked vacuolar degeneration of renal tubular epithelial cells, and atrophic glomeruli. These observations are in accordance with an earlier study that revealed long-term treatment with ETP resulted in histological alterations in kidneys that are characterized by dilation and enlargement of the proximal convoluted tubules lumen and vacuolar degeneration in their epithelium around nucleus, glomerular atrophy, necrosis, and marked congestion of the glomeruli (Kamble et al, 2013). The possible mechanism of ETP-induced toxicity is suggested to be due to its highly reactive metabolites.…”
Section: Discussionsupporting
confidence: 92%
“…Etoposide (ETO) was fabricated by Ebewe Pharma-Egypt and was sold as a colorless solution and stockpiled in the ward or the pharmacy; the injection was reserved in a cool dry place where the temperature stayed below 25 °C and secured from light according to the leaflet. ETO was given as intraperitoneal infusions at 50 mg/kg body weight/twice a week [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The animals that were intramuscularly (im) injected inside the left hip with APAN (30 mg/kg bw/twice a week) for two weeks were categorized in one group (APAN). The mice that were injected intraperitoneally (ip) with ETO for two weeks (50 mg/kg bw/twice a week) [ 22 ] were categorized as one group (ETO). The mice that were injected with both the APAN analog (15 mg/kg bw/im, twice a week) inside the hip and ETO (25 mg/kg bw/ip, twice a week) for two weeks were categorized as one group (APAN+ETO).…”
Section: Methodsmentioning
confidence: 99%